PERAN LAYANAN BIMBINGAN KELOMPOK TERHADAP KEPERCAYAAN DIRI SISWA DI KELAS VII A SMP NEGERI 1 ANGKINANG KABUPATEN HULU SUNGAI SELATAN - Runi Pirnadi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2017)
The problem to be studied is group counseling services to students' self confidence in SMP Negeri 1 Angkinang. The main purpose of this research is to know the form of group counseling services to students' self confidence in SMP Negeri 1 Angkinang.Data analysis technique used in this research is qualitative description method. The place of this research is in SMP Negeri 1 Angkinang. Objects in this study is a form of self-confidence. While the subjects in this study were principals, guidance and counseling teachers and 6 students consisting of 3 men and 3 women in one group in class VII A Lesson 2015/2016. Techniques of data collection using observation, interviews, and documentation. Data analysis techniques using descriptive analysis.The results of this research are: (1) With guidance counseling group guidance counseling service SMP Negeri 1 Angkinang overcome the problem of confidence feels easier, effective and efficient eg there are some students have the same problem bk teachers can directly address the problem at the same time . (2) The form of group counseling services to students' self-confidence in SMP Negeri 1 Angkinang is counseling and counseling teachers in cooperation with school personnel such as giving direction to parents / guardians, including in school personnel ie principals, teachers of study and homeroom. Furthermore, it is suggested that guidance and counseling teachers can improve group counseling services to students' self confidence in SMP Negeri 1 Angkinang and cooperate with principals, homeroom teachers, parents so that students behave well and become outstanding students.